2020
DOI: 10.1016/j.annemergmed.2020.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Excess Out-of-Hospital Mortality and Declining Oxygen Saturation: The Sentinel Role of Emergency Medical Services Data in the COVID-19 Crisis in Tijuana, Mexico

Abstract: Objective Emergency medical services (EMS) may serve as a key source of real-time data about the evolving health of COVID-19 affected populations, especially in low-and-middle-income countries (LMICs) with less rapid and reliable vital statistic registration systems. Although official COVID-19 statistics in Mexico report almost exclusively in-hospital mortality events, excess out-of-hospital mortality has been identified in other countries, including one EMS study in Italy that showed a 58% increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 26 publications
3
57
0
4
Order By: Relevance
“…Baldi et al compared the number of pronouncements in Lombardi, Italy in a two-month period from the end of February to the end of April during COVID19 in 2020 with the same period in 2019 and found a 62% increase, which is considerably less than our 183% increase [ 13 ]. Friedman et al found a 145% increase in out-of-hospital deaths in Tijuana following arrival of COVID19 there [ 14 ]. In the six-week period of the pandemic in Paris, compared to the same six-week periods in 2012–2020 prehospital deaths following OHCA increased 54% [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Baldi et al compared the number of pronouncements in Lombardi, Italy in a two-month period from the end of February to the end of April during COVID19 in 2020 with the same period in 2019 and found a 62% increase, which is considerably less than our 183% increase [ 13 ]. Friedman et al found a 145% increase in out-of-hospital deaths in Tijuana following arrival of COVID19 there [ 14 ]. In the six-week period of the pandemic in Paris, compared to the same six-week periods in 2012–2020 prehospital deaths following OHCA increased 54% [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to data from the Office of National Statistics (ONS) and Public Health England, occupation and socio-economic deprivation play key roles in the risk of COVID-19 infection and poor outcomes in BAME communities [ 25 , 26 ]. In Latin America mortality during the COVID-19 pandemic is reported to be higher in low socio-economic status neighbourhoods and rural communities [ 27 , 28 ]. Limited access to health care, greater social mixing, unemployment, and lower ability to work from home in the vulnerable populations are likely relevant in conferring this increased risk [ 29 ].…”
Section: Syndemics and Syndemogenesis To Understand Covid-19 Risk Inmentioning
confidence: 99%
“…Despite the biological plausibility on which we built the grounds for our hypothesis, we acknowledge its speculative nature as a potential field for future research. However, it is safe to conclude from our data that clinicians should be aware of nondyspnogenic acute hypoxemic respiratory failure in COVID-19 and possibly increase surveillance mechanisms (e.g., pulse oximetry monitoring), particularly in highrisk populations (46). Assuming that further studies would confirm the hypothesis that SARS-CoV-2 infection is associated with marked respiratory autonomic dysfunction, we could also expect cardiovascular autonomic dysfunction to participate in the pathophysiology of cardiovascular manifestations, including heart failure and cardiac arrhythmias, and related clinical outcomes.…”
Section: Potential Clinical Implicationsmentioning
confidence: 84%